2019
DOI: 10.1101/gad.322024.118
|View full text |Cite
|
Sign up to set email alerts
|

The histone chaperone CAF-1 cooperates with the DNA methyltransferases to maintain Cd4 silencing in cytotoxic T cells

Abstract: The transcriptional repression of alternative lineage genes is critical for cell fate commitment. Mechanisms by which locus-specific gene silencing is initiated and heritably maintained during cell division are not clearly understood. To study the maintenance of silent gene states, we investigated how the Cd4 gene is stably repressed in CD8 + T cells. Through CRISPR and shRNA screening, we identified the histone chaperone CAF-1 as a critical component for Cd4 repression. We found that the large subunit of CAF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…Additionally, this same study identified C/EBPa as a key regulator in lineage restriction, consistent with our identified role of C/EBPa in promoting differentiation of GMPs upon CAF-1 suppression or Hoxa9 inactivation. Based on these results and previous studies of CAF-1 dependent regulation of cellular plasticity (Cheloufi et al, 2015, Ishiuchi et al, 2015, Cheloufi and Hochedlinger, 2017, Ng et al, 2019, we speculate that perturbing CAF-1 may present a broadly applicable approach to discern transcriptional programs that are central to differentiation of various precursor cells into progressively more lineage-restricted progeny. This is noteworthy since most previous studies that investigated the function of CAF-1 in maintenance of cell identity did not probe the effect of CAF-1 ablation in progenitor -differentiated cell paradigms (Ishiuchi et al, 2015, Cheng et al, 2019, Ng et al, 2019, Volk et al, 2018.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Additionally, this same study identified C/EBPa as a key regulator in lineage restriction, consistent with our identified role of C/EBPa in promoting differentiation of GMPs upon CAF-1 suppression or Hoxa9 inactivation. Based on these results and previous studies of CAF-1 dependent regulation of cellular plasticity (Cheloufi et al, 2015, Ishiuchi et al, 2015, Cheloufi and Hochedlinger, 2017, Ng et al, 2019, we speculate that perturbing CAF-1 may present a broadly applicable approach to discern transcriptional programs that are central to differentiation of various precursor cells into progressively more lineage-restricted progeny. This is noteworthy since most previous studies that investigated the function of CAF-1 in maintenance of cell identity did not probe the effect of CAF-1 ablation in progenitor -differentiated cell paradigms (Ishiuchi et al, 2015, Cheng et al, 2019, Ng et al, 2019, Volk et al, 2018.…”
Section: Discussionsupporting
confidence: 72%
“…However, studies of CAF-1 function in mammalian tissue homeostasis have been aggravated due to its requirement during DNA replication and hence its essential role in cell proliferation and organismal development (Houlard et al, 2006, Volk et al, 2018, Cheloufi and Hochedlinger, 2017. Recent studies of embryonic stem cell (ESC) differentiation and T cell development uncovered additional roles of CAF-1 in cooperating with chromatin-modifying enzymes, such as the polycomb repressive complex 2 (PRC2), histone deacetylases (HDAC1/2), the histone demethylase LSD1 and DNA methyltransferase (Cheng et al, 2019, Ng et al, 2019. However, how these activities of CAF-1 might be coupled to the action of transcription factors and regulation of cellular identity in normal homeostasis remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol described in this section was only used for experiments shown in Figure 2F and Figure S2A-D. sgRNAs were designed using the Crispr guide design software (http://crispr.mit.edu/). sgRNA encoding sequences were cloned into the retroviral sgRNA expression vector pSIN-U6-sgRNAEF1as-Thy1.1-P2A-Neo that has been reported before (Ng et al, 2019). To make the double sgRNA vector for experiments shown in Figures S2A-D, the sgRNA transcription cassette, ranging from the U6 promoter to the U6 terminator, was amplified (primer sequences can be found in the Key Resources Table) and cloned into the pSIN vector after the first sgRNA encoding cassette.…”
Section: Retroviral Transduction and 2d2 Tcrtg Cas9 Tg T Cell-mediatementioning
confidence: 99%
“…RBBP4, also known as RbAp48, is named for its ability to bind to retinoblastoma proteins in vivo and in vitro [ 20 ]. Previous studies showed that the RBBP4 protein is a component of a variety of complexes involved in chromatin assembly, remodeling, and nucleosome modification, such as SIN3[ 21 ], polycomb repressor complex 2[ 22 , 23 ], histone acetyltransferase 1[ 24 ], and chromatin assembly factor 1[ 25 ] and plays a different role in each complex. It has been demonstrated that RBBP4 expression is upregulated and correlated with the malignant phenotypes in many types of human tumors, such as lung cancer[ 26 ], liver cancer[ 27 ], thyroid carcinoma[ 28 ], and acute lymphoblastic leukemia[ 29 ].…”
Section: Discussionmentioning
confidence: 99%